Two new records of the genus Kamendaka (Hemiptera: Auchenorrhyncha: Derbidae) from Korea with a key to the Korean species - Park, Jaekook; Jung, Sunghoon (Journal of Asia-Pacific biodiversity, 2023)
Two new records of the genus Kamendaka Distant, K. aculeata Yang & Wu and K. annulata Yang & Wu, are recorded from Korea for the first time. The morphological information, such as the diagnosis of male habitus and genitalia, is provided with photographs, and a key to the Korean species of the genus Kamendaka is presented.